Modeling of non-equilibrium effects in particulate flow through porous media - Jin, Yi (My University, 2018)
The complex dynamics of fluid and particles flowing through pore space demands some relaxation time for particles to catch up with fluid velocity which manifest themselves as non-equilibrium (NE) effect. Previous studies have shown that NE effect in particulate transport can have significant consequences when relaxation time is comparable to the characteristic time associated with the fluid flow field. However, the existing models are lacking to account for this complicated relation between particles and fluid. In this thesis study, the general form of harmonic oscillation equation is adapted to describe NE effects in particulate flow system. The NE effect is evaluated by solving coupled mass balance equations with computational fluid dynamic (CFD) techniques within COMSOL Multiphysics®. Simplified straight tube model, periodic converging-diverging tube model and SEM image of a real pore network are applied in the NE analyses. The results indicate that two key parameters of oscillator equation, amplitude (A) and damping ratio (ζ) can be used to explain the NE effect between particle and fluid. The former parameter represents the magnitude of NE and the latter is an indication of flow path geometry as well as time needed to attain equilibrium. The sensitivity analyses imply that fluid viscosity, flow channel size, and flow pattern affect the magnitude of the NE effect. By conducting simulation on the SEM image of a real pore structure, the equivalent radii of the pores that particles move through were obtained.
Keywords: Petroleum Engineering; Particulate Flow; Non-Equilibrium; Computational Fluid Dynamics (CFD)